Comparative analysis of indonesian and chinese idioms containing the human body part "eye" - Hu Ri Lan; Suroso (International Journal of Education, Vocational and Social Science, 2025)
This study aimed to explore the connotations of idioms containing the human body part "eye" in Indonesian and Chinese. Understanding idioms containing the human body part "eye" is crucial in cross-cultural communication, helping to avoid misunderstandings and enhance understanding of different cultural values. The authors used semantic analysis to describe the connotations of idioms containing the word "eye." The data for this study were collected from Indonesian and Chinese articles in dictionaries, news articles, short stories, and online opinion pieces. The results showed that significant differences between idioms containing the “eye” element in Indonesian and Chinese.Chinese idioms showcase linguistic beauty through their philosophically rich forms and meanings,while Indonesian idioms demonstrate cultural diversity with their flexible,adaptable structures and everyday-life connotations.